2017
DOI: 10.1515/cercles-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of translanguaging practices in an online beginner-level foreign language classroom

Abstract: Translanguaging, the movement between communicative modes and features of different languages, is becoming an established research tradition in content-focused second language learning contexts. Pedagogic translanguaging practices nevertheless remain under-applied and under-researched in foreign language instructional settings, whether face-to-face or online. Synchronous virtual foreign language classrooms represent particularly rich spaces in which to begin to explore such practices, due to their multimodal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Although translanguaging and code-switching have been largely researched in language classrooms (Adinolfi & Astruc, 2017;Canagarajah, 2011;García & Kleyn, 2016;García & Lin, 2016;Kramsch & Huffmaster, 2015;Liebscher & Dailey-O'Cain, 2005), and in CMC (Kötter, 2003;Rao et al, 2016;Zheng et al, 2017), research on translanguaging in online SCMC and VEs is scarce. This section details the few studies which have examined different aspects of translanguaging in oral and written interactive tasks in online or hybrid settings.…”
Section: Translanguaging In Scmcmentioning
confidence: 99%
See 1 more Smart Citation
“…Although translanguaging and code-switching have been largely researched in language classrooms (Adinolfi & Astruc, 2017;Canagarajah, 2011;García & Kleyn, 2016;García & Lin, 2016;Kramsch & Huffmaster, 2015;Liebscher & Dailey-O'Cain, 2005), and in CMC (Kötter, 2003;Rao et al, 2016;Zheng et al, 2017), research on translanguaging in online SCMC and VEs is scarce. This section details the few studies which have examined different aspects of translanguaging in oral and written interactive tasks in online or hybrid settings.…”
Section: Translanguaging In Scmcmentioning
confidence: 99%
“…Adinolfi and Astruc (2017) examined translanguaging practices in a beginner‐level Spanish online audio‐based synchronous lesson delivered through a videoconferencing tool. The analysis of teacher–student and student–student interactions revealed frequent use of translanguaging on the part of the teachers, mainly when giving instructions and prompting nonverbal responses, whereas students rarely exhibited any instances of translanguaging.…”
Section: Introductionmentioning
confidence: 99%
“…Such practice of exploiting various repertoire is also evident in Adinolfi & Astruc who found that during the course of the learning process, students and teachers did codeswitching between English and Spanish. 21 Moreover, Saputra & Akib also found in their study that teachers mixed language repertoire in the learning process through both intersentential and intransentential codeswitching between Indonesian, English, and local language. 22 In short, language repertoires are exploited in classroom interaction by mixing them or translating from one repertoire to another.…”
Section: Resultsmentioning
confidence: 91%
“…Learning through microclasses allows students to adjust their learning speed according to their own basis and habits, and personalized learning is supported; in addition, microclasses can enhance the initiative of students in learning. erefore, the application of microclasses to teaching not only conforms to the view that "students are the subject of cognitive process and the active constructor of meaning" [17] in the constructivist theory but can also take into account the differences between students. It can be said to coincide with each other.…”
Section: Constructivist Eorymentioning
confidence: 85%